Analisis Usahatani Padi Sawah di Desa Telutu Jaya Kecamatan Tinanggea Kabupaten Konawe Selatan - Irmawati, Irmawati; Tuwo, Muhammad Akib; Fyka, Samsul Alam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This research was conducted on March-April 2017, it aims to: 1) knowing the factors that affect rice production. 2) knowing the efficiency level of using production factors in rice farming. The method of this research is using the survey method, and the method of sample is using simple random sampling methods by as much as 36 people. The analysis tool that used is a function of the Cobb Douglas production and efficiency analysis of rice farming. The results showed that: 1) commodious area variables, seed, and urea fertilizer is real influential toward rice farming production, whereas the factors of production on using KCl fertilizer, SP 36 fertilizer, pesticides, and labor real has no effect toward rice production. 2) the use of production factors on rice farming (seed, and urea fertilizer) are on a condition that is not efficient. The use of inefficient production factors can cause low productivity so that rice farming production levels become low.